Hybrid carrageenans : isolation, chemical structure, and gel properties - Hilliou, L. (2014)
Hybrid carrageenan is a special class of carrageenan with niche application in food industry. This polysaccharide is extracted from specific species of seaweeds belonging to the Gigartinales order. This chapter focuses on hybrid carrageenan showing the ability to form gels in water, which is known in the food industry as weak kappa or kappa-2 carrageenan. After introducing the general chemical structure defining hybrid carrageenan, the isolation of the polysaccharide will be discussed focusing on the interplay between seaweed species, extraction parameters, and the hybrid carrageenan chemistry. Then, the rheological experiments used to determine the small and large deformation behavior of gels will be detailed before reviewing the relationships between gel properties and hybrid carrageenan chemistry.